Density, Refractive Index, pH, and Cloud Point Temperature Measurements and Thermal Expansion Coefficient Calculation for PPG400, PE62, L64, L35, PEG400, PEG600, or PEG1000+ Water Systems - De Oliveira, Leonardo H. (2021)
Thermophysical properties and phase behavior of seven {polymer (1) + water (2)} systems were determined using PPG400, Ultraric PE62, Pluronic L64, Pluronic L35, PEG400, PEG600, and PEG1000. Density (ρ) and refractive index (n) were measured for the whole range of w1 at T = 293.2 K. Correlation with Redlich-Kister equation and prediction with Lorentz-Lorenz theoretical model were done. pH was measured for different mass fractions at ambient temperature (T ≈ 298.2 K). Cloud point temperature (Tcloud) was measured for different polymer mass fractions (w1) from 0.02 up to 0.30. The thermal expansion coefficient (αT) was calculated for w1 = 0.15 and temperature (T) from 278.2 up to 348.2 K. Experiments were conducted at atmospheric pressure (P ≈ 95 kPa). The obtained thermophysical properties indicate that PEGs + water have the highest ρ while PPG400 + water has the smallest ρ. Also, all ρ vs w1 curves present a maximum value. n profiles are similar for all systems, showing the same refractive index increment for w1 below 0.4. Density (Δρ) and refractive index (Δn) deviations are higher for the PPG400 + water system, mainly due to the highest propylene content and hydrophobic character of PPG units. Moreover, pH varies with polymer mass fraction reaching a minimum value, probably because polymers release H+ in solution. Phase transition results indicate that Tcloud and αT present related behaviors, i.e., when solution became turbid, αT shows an abrupt change in slope.